The Civilizational Role of the Temple in Mesopotamian Society - Semicha , Fayza (The Algerian Historical Journal, 2026)
The Mesopotamian temple held a privileged position as a landmark, reflecting the religious, social, and economic life of its society. It was regarded as the house of the deity and a sacred center for rituals, yet its role extended beyond worship to daily life. Over time, it became a vast economic institution, owning land, managing resources, and organizing agricultural and distribution activities. The temple also served as an administrative center maintaining social and political order. Its architectural and artistic features demonstrate creativity and symbolism, carrying both religious and political significance. Overall, the temple reflects the interconnected nature of religion, economy, and governance in Mesopotamia.